#TITLE_ALTERNATIVE# - NAPITUPULU (NIM: 13206143) Pembimbing : Dr. Achmad Munir ; Dr. Trio Adiono, MANGASI
The increasing need of wireless data communication and the emerging new high speed wireless telecommunication technology such as WiMAX, have made the need of smaller yet versatile devices increased. One of the most important elements on every wireless telecommunication devices is antenna. Therefore a dual band compact inverted-F antenna for WiMAX 2.3 GHz and 3.3 GHz is designed in this final project as the answer for the need for smaller and multi frequency antenna. The designing process is carried out using 3D software. The prototype of the final design is fabricated and tested to be compared with the simulation result. Within the designing process, parametric study about the effect of every antenna’s elements dimension to the antenna’s performance is carried out. The result shows that the dual band compact inverted-F antenna can be viewed as a combination of asymmetric dipole antenna and inverted-L antenna (ILA) that each of them are responsible for the control of the higher band and the lower band characteristic. The result of the parametric study is used to determine the optimized final design to be proposed. The final proposed antenna design operate from 2.16 GHz to 2.58GHz and from 3.14GHz to 4GHz, with the lower and higher band gain is from -1.05 dB to (-0.69 dB) and from 2.07 dB to 2.32 dB , respectively.